The effects of tax audit and investigation activities on individual tax compliance : evidence from Malaysia / Razilina A. Razak, Zaleha Abdul Shukor and Norsiah Ahmad. - A. Razak, Razilina; Abdul Shukor, Zaleha; Ahmad, Norsiah (Universiti Teknologi MARA Cawangan Selangor, 2012)
Tax non-compliance presents a major problem because it undermines the effectiveness of a country's macroeconomic policy. Tax non-compliance is not only affected by economic factors, but also by tax dministration and individual psychological factors. Employing the Reintegrative Shaming Theory, a survey was conducted on individual taxpayers who had experienced either being audited or investigated by the Inland Revenue Board Malaysia (IRBM). Findings on the 172 respondents indicated if taxpayers perceived their experience with tax enforcement to be reintegrative, they tended to be tax compliant in the long run. However, if taxpayers perceived tax enforcement to be stigmatized, no significant association between such an experience and future tax compliance was found. In addition, feelings of resentment either towards tax authority or tax laws tended to have a mediating effect between the perception of reintegrative enforcement experience and the tendency for tax compliance. These findings suggested that the IRBM should seriously consider an enforcement method that is of reintegrative, rather than stigmatized nature, to effectively nurture compliance among individual taxpayers.